Evaluación técnica y financiera sobre la producción de suero en polvo partiendo de lactosuero generado en el proceso de fabricación de leche de búfala (2019)
This project aims to contribute to the recovery and use of an industrial waste such as whey, through the production of protein powder from buffalo whey. The whey is a byproduct of cheese making, and it is a residue with a high nitrogen load, which, having a high load of this compound, can increase COD in water sources and in agricultural fields causing damage of flora and fauna in the ecosystem. That is why a decision is made; which, through the biochemical transformation of the residual whey through several extraction processes at the laboratory level, concentrated protein powder will be obtained. Allowing also to generate an idea for the construction of a company being this product widely used for the food, pharmaceutical and supplementary food industries for high performance athletes. Contributing to research in the biochemical and food area within the Fundación Universidad de América.